Pengaruh Konsentrasi Minyak Daun Cengkeh dalam Lilin Cair Minyak Goreng Bekas Terhadap Kepadatan Lalat di Empat Warung Makan di Pantai Depok Yogyakarta - Riezka Danastri Primastuti; Lilik Hendrarini; indah Werdiningsih (Sanitasi: Jurnal Kesehatan Lingkungan, 2014)
Fly is insect which can play role as vector in the transmission of several diseases. Based on the preliminary survey in a food stall at Depok Beach of Parangtritis, the density of flies was obser-ved 10 per 1 m2 dining table which was categorized as high population and therefore need to be controlled. This study used clove leave oil, a plant-based repellent, for controlling the flies as it contains 80 – 85 % eugenol which gives pungent scent and has function to repel flies. The oil was mixed into liquid wax made from used cooking oil. The research method was an experi-ment which followed pre-test and post-test with control group design. The study was conduc-ted at four food stalls which were selected by using purposive sampling method, because they were the closest to the fresh fish market of the beach. In the first three sampled food stalls, three experimental groups, i.e. three variation of clove oil concentration (10 %, 12 % and 14 %), were applied; meanwhile the fourth food stall was for the two control groups (i.e. solid wax and not-burned clove leaf oil). The fly densities were measured before and after the treatment in each group were carried out and the study was held in 20 days observation with five-day place-ment rotation. The results showed that the average decrease percentage of fly density yielded from the three clove oil concentration, were 47,32 %, 57,18 %, and 69,93 %, respectively. The one way anova statistical test obtained ? value less than 0,001; which means that those per-centages were significant. The post-hoc test with LSD concluded that the most effective con-centration was 14 %, i.e. the mixture of 7 ml clove leaf and 43 ml used cooking oil.